Genipin and insulin combined treatment improves implant osseointegration in type 2 diabetic rats - Zhang, Jiajia (J Orthop Surg Res, 2021)
BACKGROUND: Type 2 diabetes mellitus (T2DM) has a harmful effect on the stability and osseointegration of dental implants. T2DM induces mitochondrial damage by inhibiting AMPK signaling, resulting in oxidative stress and poor osteogenesis in the peri-implant bone area. Genipin is a major component of gardenia fruits with strong antioxidant, anti-inflammation, and antidiabetic actions, and it also can activate mitochondrial quality control via the AMPK pathway. The purpose of this study was to investigate the effects of genipin and insulin treatment on implant osseointegration in T2DM rats and explore the underlying mechanisms. METHODS: Streptozotocin-induced diabetic rats received implant surgery in their femurs and were then assigned to five groups that were subjected to different treatments for three months: control group, T2DM group, insulin-treated T2DM group (10 IU/kg), genipin-treated T2DM group (50 mg/kg), and the genipin and insulin combination-treated T2DM group. Then, we regularly assessed the weight and glucose levels of the animals. Rats were euthanized at 3 months after the implantation procedure, and the femora were harvested for microscopic computerized tomography analysis, biomechanical tests, and different histomorphometric assessment. RESULTS: The results indicated that the highest blood glucose and oxidative stress levels were measured for the T2DM group, resulting in the poorest osseointegration. The combination-treated T2DM group mitigated hyperglycemia and normalized, reactivated AMPK signaling, and alleviated oxidative stress as well as reversed the negative effect of osseointegration. There were beneficial changes observed in the T2DM-genipin and T2DM-insulin groups, but these were less in comparison to the combination treatment group. CONCLUSION: Our study suggests that treatment with genipin in combination with insulin could be an effective method for promoting implant osseointegration in T2DM rats, which may be related to AMPK signaling.